2017
DOI: 10.1007/s10555-017-9689-6
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-related carcinogenesis in head and neck cancer

Abstract: Head and neck cancer (HNSCC) is a devastating disease. Patients require intensive treatment that is often disfiguring and debilitating. Those who survive are often left with poor speech articulation, difficulties in chewing and swallowing, cosmetic disfigurement, as well as loss of taste. Furthermore, given that HNSCC survivors are frequently disabled and unable to return to work, the economic and societal costs associated with HNSCC are massive. HNSCC is one of many cancers that are strongly associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
180
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(194 citation statements)
references
References 40 publications
4
180
0
10
Order By: Relevance
“…An increased number of head and neck reconstructions could be attributed to the higher rate of smokers in the HT group, since smoking significantly increases the risk of cancer. 48 Patients in the NT group required significantly higher numbers of lower extremity reconstructions that probably results from significantly more defects after trauma in this group. In the future, prospective studies and pooling data of large microsurgical centers could help to further elucidate the impact of hypothermia on outcome of different free flap entities, also regarding the recipient sites.…”
Section: Discussionmentioning
confidence: 85%
“…An increased number of head and neck reconstructions could be attributed to the higher rate of smokers in the HT group, since smoking significantly increases the risk of cancer. 48 Patients in the NT group required significantly higher numbers of lower extremity reconstructions that probably results from significantly more defects after trauma in this group. In the future, prospective studies and pooling data of large microsurgical centers could help to further elucidate the impact of hypothermia on outcome of different free flap entities, also regarding the recipient sites.…”
Section: Discussionmentioning
confidence: 85%
“…Tobacco smoking is a risk factor for the occurrence and increases the incidence of various cancers, including bladder [1], head and neck [2], lung [3], and pancreatic cancer [4]. Tobacco smoking contains many carcinogenic chemicals that can create a specific mutational signature and increase the somatic mutational burden associated with unrepaired DNA damage [5].…”
Section: Introductionmentioning
confidence: 99%
“…With this rational in view, validation of the present in silico observations was sought to be done by quantifying the level of 8-OHdG in DNA digests of cancer cells obtained from patients with different GSTP1 genotypes. Presence of significantly higher level of 8-OHdG in cancer DNA samples with AA-genotypes suggested that metabolic activation of RAN/tobacco in the oral cavity could produce a variety of toxic substances which induce various damages 42,43 including 8-OHdG 44 . This could be the reason for higher 8-OHdG observed in tumor DNA than DNA from peripheral blood of the same patient.…”
Section: Discussionmentioning
confidence: 99%